Measurement performance of activity measurements with newer generation of Apple watch in wheelchair users with spinal cord injury: manually and device-counted pushes [data] - Benning, Nils-Hendrik; Knaup-Gregori, Petra; Rupp, Rüdiger (Universität, 2021)
This dataset contains the results (manually counted pushes and pushes counted by Apple Watch Series 4) of the study presented in the paper "Accurac...
Gesehen am 10.03.2022
Keywords: Forschungsdaten; Datenbank